Effects of CO2 Enrichment on Carbon Assimilation, Yield and Quality of Oriental Melon Cultivated in a Solar Greenhouse - Xintong Han; Yue Sun; Junqin Chen; Zicong Wang; Hongyan Qi; Yufeng Liu; Yiling Liu (Horticulturae, 2023)
Since CO2 is the fundamental substrate for photosynthesis, fluctuating concentrations have a direct effect on plant growth and metabolism. Accordingly, CO2 enrichment within a certain range was found to improve photosynthesis, yields and the quality of plants. In order to further understand the underlying impact of CO2 enrichment, this study employed an open-top chamber growth box model with the following two treatments: control treatment (CO2 concentration: 380 ± 30 μL/L) and CO2 enrichment (1200 ± 50 μL/L). The effects on leaf carbon assimilation, fruit yield and quality were subsequently determined. The net photosynthetic rate, intercellular CO2 concentration, dry matter accumulation and soluble sugar content in the oriental melon leaves increased significantly on day 5 of CO2 enrichment. Moreover, a significant increase in the activity of carbon assimilation-related enzymes Rubisco, RCA, FBPase and CA was also observed, with the upregulation of CmRubisco, CmRCA, CmFBPase and CmCA gene expression from day 15 of CO2 enrichment. Thus, the yield per plant and content of soluble sugars and soluble solids in the fruit also increased significantly. These findings suggest that CO2 enrichment has positive effects on oriental melon growth, increasing photosynthesis and the activity of photosynthetic carbon-assimilation-related enzymes and associated gene expression, thereby improving fruit yields and quality. These results provide a foundation for the CO2 enrichment of oriental melon cultivated in solar greenhouses in autumn/winter and winter/spring.